The Teacher’s Roles in Teaching English for Specific Purposes to Nursing Program Students - Nurul Arifah; V. Luluk Prijambodo (Magister Scientiae, 2014)
The consideration of mastering English nowadays brings advanced concept in order to reach better education and career in globalization era and the mindset changes of English language education, particularly in nursing as a familiar job within public health. Related to that phenomenon, English for Specific Purposes (ESP) teacher should also notice that in teaching ESP they have to play their roles to help students in the teaching and learning process. Considering the importance of the teacher’s roles in teaching ESP, this study aimed at finding out the teacher’s roles in the teaching and learning process of ESP to nursing program students. Besides, this study also aimed at finding out the students responses towards the roles in the teaching and learning process of ESP to nursing program students. This qualitative case study focuses primarily on understanding in depth the teacher’s roles in the teaching and learning process of ESP to nursing program students. The data to cope with ‘the roles played by the teacher in the teaching of ESP’ were both verbal and nonverbal performance when the teachers were playing their roles in classroom while the data to deal with ‘the students’ response towards the teacher’s roles’ were the students’ opinion and attitude towards the teachers’ performance in the classroom. For both research questions, the data collection and analysis procedures were done using classroom observations (using audio visual recording, observation sheet, and fields note), questionnaire and interview (for both the teacher and students). This study found that the kinds of roles played by the research subjects were as the lecturer, clinical or practical teacher, role model, facilitator, mentor, assessor, curriculum assessor, resource developer, and study guide producer. This study also found that the students’ responses towards the teacher’s roles were that they liked when the teacher could do their roles well in the class. The students could also be able to understand their response towards the teacher’s roles that would have impact to their learning process, thus they became active and enthusiastic. While each of the nine of the eleven roles played has been described separately, in reality they are often interconnected and closely related one to another. The teacher’s roles in the teaching and learning process of ESP to nursing program students could be used by teachers as